A model-based cost-effectiveness analysis of osteoporosis screening and treatment strategy for postmenopausal Japanese women. Issue 2 (February 2017) - Yoshimura, M.; Moriwaki, K.; Noto, S.; Takiguchi, T.
Abstract Summary Although an osteoporosis screening program has been implemented as a health promotion project in Japan, its cost-effectiveness has yet to be elucidated fully. We performed a cost-effectiveness analysis and found that osteoporosis screening and treatment would be cost-effective for Japanese women over 60 years. Introduction The purpose of this study was to estimate the cost-effectiveness of osteoporosis screening and drug therapy in the Japanese healthcare system for postmenopausal women with no history of fracture. Methods A patient-level state transition model was developed to predict the outcomes of Japanese women with no previous fracture. Lifetime costs and quality-adjusted life years (QALYs) were estimated for women who receive osteoporosis screening and alendronate therapy for 5 years and those who do not receive the screening and treatments. The incremental cost-effectiveness ratio (ICER) of the screening option compared with the no screening option was estimated. Sensitivity analyses were performed to examine the influence of parameter uncertainty on the base case results. Results The ICERs of osteoporosis screening and treatments for Japanese women aged 50–54, 55–59, 60–64, 65–69, 70–74, and 75–79 years were estimated to be 89, 242, 64, 010, 40, 596, 27, 697, 17, 027, and 9771 per QALY gained, respectively. Deterministic sensitivity analyses showed that several parameters such as the disutility due to vertebral fracture had a significant influence on the base case results. Applying a willingness to pay of 50, 000 per QALY gained, the probability that the screening option became cost-effectiveness estimated to 50.9, 56.3, 59.1, and 64.7 % for women aged 60–64, 65–69, 70–74, and 75–79 years, respectively. Scenario analyses showed that the ICER for women aged 55–59 years with at least one clinical risk factor was below 50, 000 per QALY. Conclusions In conclusion, dual energy X-ray absorptiometry (DXA) screening and alendronate therapy for osteoporosis would be cost-effective for postmenopausal Japanese women over 60 years. In terms of cost-effectiveness, the individual need for osteoporosis screening should be determined by age and clinical risk factors.